Synthesis and antitumor efficacy of daunorubicin-loaded magnetic nanoparticles - Jun Wang (Dove Medical Press, 2011)
Jun Wang1, Baoan Chen1, Jian Chen1, Xiaohui Cai1, Guohua Xia2, Ran Liu1, Pingsheng Chen2, Yu Zhang3, Xuemei Wang31Department of Hematology and Oncology, Zhongda Hospital, School of Medicine, Southeast University, Nanjing, China 210009; 2Medical School, Southeast University, Nanjing; 3State Key Laboratory of Bioelectronics, Southeast University, Nanjing, China 210009Background: A promising approach to optimize the disposition of daunorubicin-loaded magnetic nanoparticles (DNR-MNPs) was developed to minimize serious side effects of systematic chemotherapy for cancer.Methods: The physical properties of DNR-MNPs were investigated and their effect on leukemia cells in vitro was evaluated by a standard WST-1 cell proliferation assay. Furthermore, cell apoptosis and intracellular accumulation of DNR were determined by FACSCalibur flow cytometry.Results: Our results showed that the majority of MNPs were spherical and their sizes were from 10 to 20 nm. The average hydrodynamic diameter of DNR-MNPs in water was 94 nm. The in vitro release data showed that the DNR-MNPs have excellent sustained release property. Proliferation of K562 cells was inhibited in a dose-dependent manner by DNR in solution (DNR-Sol) or by DNR-MNPs. The IC50 for DNR-MNPs was slightly higher than that for DNR-Sol. DNR-MNPs also induced less apoptosis in K562 cells than did DNR-Sol. Detection of fluorescence intensity of intracellular DNR demonstrated that DNR-MNPs could be taken up by K562 cells and persistently released DNR in cells.Conclusion: Our study suggests that optimized DNR-MNPs formulation possesses sustained drug-release and favorable antitumor properties, which may be used as a conventional dosage form for antitumor therapy.Keywords: daunorubicin, magnetic iron oxide nanoparticles, drug delivery system, target selection, K562 cells